Color Stability of Bulk Fill Composite Resins Submitted to Coffee Staining - Arruda, Beatriz Maria; Bassi, Julio Cesar; Vitti, Rafael Pino; Scatolin, Renata Siqueira (Brazilian Dental Science, 2020)
Objective: The aim of this in vitro study was to evaluate the color stability of different bulk fill composite resins after extrinsic staining with coffee. Material and methods: Forty-eight disk-shaped specimens (6 mm diameter x 2 mm thick) of each composite resin were prepared for color change test. The composite resins were divided into 4 groups (n=12): one conventional composite resin (Filtek Z250) and three bulk-fill composite resins (Filtek Bulk Fill, Aura Bulk Fill, and Opus Bulk Fill). The samples were stained with 20 mL coffee solution for 7 days, with the solution being replaced every 24 h. The color change analysis was performed using a spectrophotometer, according to the CIE Lab formula. Data were analyzed using the Analysis of variance (ANOVA) and Tukey HSD tests (?=0.05). Results: The results revealed significant differences in color change among the composite resins tested (?<0.0001). The Aura Bulk Fill and Opus Bulk Fill showed the highest color change values. Conclusions: Thus, all the resins analyzed were susceptible to extrinsic staining with coffee, and the Filtek Bulk Fill showed the lowest color change value.